Effect Of Topical DLBS 1425 On Tissue Plasminogen Activator (tPA) Expression In Trabecular Meshwork Of Wistar Rats - Widijanto, Utami; Nugroho, Trilaksana; Cahyono, Maharani (RSUP Dr. Kariadi, 2021)
Introduction: Tissue plasminogen activator (tPA) in the trabecular meshwork (TM) is a serine protease that important to maintain the aquos outflow resistance by activating the matrix metalloproteinase (MMP). It can cause a degradation of the extracellular matrix, which can maintain the normal flow of aquos humor. However, the use of anti-inflammatory drugs has been shown to reduce the expression of tPA, leading to an increase in the outflow resistance. Therefore, we propose the use of DLBS 1425, an extract of Phaleria macrocarpa which has been proven to have anti-inflammatory effects. Aim : This study aims to determine the expression of tPA in Wistar rats’ TM. Methods : An experimental laboratory study with post-test only randomized controlled group design was performed. Twenty-two Wistar rats were divided into two groups, the control and the experimental. The experimental group was given topical DLBS 1425 at a dose of 6 times / day, for 4 weeks. The control group was given drops of Hyalub Minidose® 6 times / day, for 4 weeks. tPA expression on TM was examined by immunohistochemical staining. Data were collected and processed using the SPSS 15.0 for Windows. Results : The mean tPA expression in TM with Allred scores in the experimental group (0.18 ± 0.60) was significantly lower (p <0.001) than the control group (6.27 ± 0.91). Conclusion : Topical DLBS 1425 suppresses the expression of tPA on the trabecular meshwork of Wistar rats. Key words: tissue plasminogen activator, trabecular meshwork, DLBS 1425, Phaleria macrocarpa.